2005
DOI: 10.1186/1465-9921-6-11
|View full text |Cite
|
Sign up to set email alerts
|

The absence of reactive oxygen species production protects mice against bleomycin-induced pulmonary fibrosis

Abstract: These results suggest that NADPH-oxidase-derived ROS are essential to the development of pulmonary fibrosis. The absence of collagen deposition in KO mice seems to be associated with an elevated MMP-9/TIMP-1 ratio in the lungs. This finding highlights the importance of metalloproteinases and protease/anti-protease imbalances in pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 32 publications
7
130
0
3
Order By: Relevance
“…That is, antioxidant compounds may attenuate oxidative damage caused directly by bleomycin, or they may limit the impact of reactive oxygen species produced by phagocytes such as macrophages and neutrophils and thus interfere with the inflammatory process. We recently reported that mice deficient in the p47 phox subunit of the NADPH oxidase complex do not develop pulmonary fibrosis after intranasal administration of bleomycin (56). This also suggests that an imbalance of the molar MMP-9/TIMP-1 ratio may influence the fibrogenic process in this model.…”
Section: Mmp-12mentioning
confidence: 84%
“…That is, antioxidant compounds may attenuate oxidative damage caused directly by bleomycin, or they may limit the impact of reactive oxygen species produced by phagocytes such as macrophages and neutrophils and thus interfere with the inflammatory process. We recently reported that mice deficient in the p47 phox subunit of the NADPH oxidase complex do not develop pulmonary fibrosis after intranasal administration of bleomycin (56). This also suggests that an imbalance of the molar MMP-9/TIMP-1 ratio may influence the fibrogenic process in this model.…”
Section: Mmp-12mentioning
confidence: 84%
“…Phosphorylation of p47 phox thereby promotes the recruitment of p67 phox by serving as an adapter and bridging p67 phox with the cyt b558 complex (80). p47 phox has been documented to be important in the progression of atherosclerosis and pulmonary fibrosis (26,268). phox , resulting in the assembly of the cytosolic regulatory proteins (p40 phox , p47 phox , and p67 phox ) with the flavocytochrome b558 (made up of the membrane-associated catalytic subunit gp91 phox and p22 phox ).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%
“…ROS generation by NOX5 and DUOX can be induced by calcium and is independent of p22 phox subunit. To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars p47 phox null mice were protected against formation of atherosclerotic lesions and development of pulmonary fibrosis (26,268). Mice deficient in p47 phox subunit or NOX2 were also protected against TNF-a-induced lung inflammation or sepsis-induced lung microvascular injury (126 469).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%
“…MMP-2 is localized in structural cells like regenerated alveolar epithelial, bronchial epithelial cells and fibroblasts. In lung fibrosis, MMP-2 could play a role in the regeneration of alveolar epithelial cells Lemjabbar et al, 1999;Manoury et al, 2005;Scabilloni et al, 2005). The expression of the two gelatinases (MMP-2 and MMP-9) at different stages of fibrosis suggests that MMP-9 could be rather linked to inflammation-induced tissue remodeling, while MMP-2 may be associated with an impaired tissue remodeling leading to pathological collagen deposition and interstitial fibrosis.…”
mentioning
confidence: 99%